2022
DOI: 10.3390/ani13010068
|View full text |Cite
|
Sign up to set email alerts
|

Animal Control and Field Services Officers’ Perspectives on Community Engagement: A Qualitative Phenomenology Study

Abstract: Very little is known about the prevalence, scope, and methods of community engagement employed by animal control and field services officers to address the issue of animal cruelty and neglect. This study used a phenomenological approach to understand how officers defined community engagement. The researchers conducted semi-structured interviews with twenty-nine animal control and field services officers. The definitions of community engagement varied greatly across this sample of U.S. officers. However, most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The importance and impact of community engagement in animal sheltering, such as strategies used by animal control and field service officers, have been previously described by Moss et al [44]. Our findings suggest that not only do interventions that engage individuals beyond the shelter's volunteers and staff lead to more successful programs, but these shorter-duration fostering interventions can significantly impact outcomes for dogs.…”
Section: Discussionsupporting
confidence: 70%
“…The importance and impact of community engagement in animal sheltering, such as strategies used by animal control and field service officers, have been previously described by Moss et al [44]. Our findings suggest that not only do interventions that engage individuals beyond the shelter's volunteers and staff lead to more successful programs, but these shorter-duration fostering interventions can significantly impact outcomes for dogs.…”
Section: Discussionsupporting
confidence: 70%
“…Due to the multi-faceted and community-specific nature of rez dog-related challenges, community engagement represents a promising approach to improving the effectiveness and sustainability of animal control/field services policies and practices on the Fort Berthold reservation [ 49 , 50 ]. A limited number of studies have discussed how community engagement strategies have been used in the animal welfare field [ 51 , 52 , 53 , 54 ]. Community engagement provides community members the opportunity to collaboratively identify issues and offer critical perspectives on the policies and practices that directly affect them.…”
Section: Discussionmentioning
confidence: 99%
“…The negative perception of the council may be perpetuated by animal control officers not being able to provide the appropriate support to communities due to policy and financial restrictions. One study indicated that animal control officers faced barriers to engaging with the community, due to a lack of funding, staff, and resources, even though many animal control officers perceived programs like the sterilization of stray cats (TNR) as good for the community [78].…”
Section: Perception Of Supportmentioning
confidence: 99%